A k-mismatch string matching for generalized edit distance using diagonal skipping method. - HyunJin Kim (PLoS ONE)
This paper proposes an approximate string matching with k-mismatches when calculating the generalized edit distance. When the edit distance is generalized, more sophisticated string matching can be provided. However, the execution time increases because of the bundle of complex computations for calculating complicated edit distances. The computational costs for finding which steps or edit distances are over k-mismatches cannot be significant in the generalized edit distance metric. Therefore, we can reduce the execution time by determining steps over k-mismatches and then skipping them. The diagonal step calculations using the pruning register skips unnecessary distance calculations over k-mismatches. The overhead of control statements and reordered memory accesses can be amortized by skipping multiple steps. Even though the proposed skipping method requires additional overhead, the proposed scheme's practical embodiments show that the execution time of string matching is reduced significantly when k is small.